Road signs : geosemiotics and human mobility - Salmiah, Abdul Hamid (Aalborg University Press, 2015)
How' do' people'make' sense' of' traffic' signs' in' urban' settings,' and' how' can' this' knowledge' be' utilized' to' inform' the' creation' of' better' design' policies' and' manuals?'These'questions'relate'to'the'theoretical'and'empirical'evidence'of'road' signs'as'traffic'guides'as'well'as'to'how'a'person'moves'around'in'an'environment.' Different'types'of'road'signs'exist'in'this'world.'Most'road'signs'are'uniform'signs' that' are' standard' for' worldwide' application,' based' on' the' Vienna' Convention' (United'Nations'Economic'Commission'for'Europe,'1968).'Many'research'studies'in' the' urban' environment' and' traffic' engineering' fields' focus' on' human' behaviour' and'traffic'sign'system'recognition.'In'order'to'provide'an'overview'of'the'stateRofR theRart'developments,'this'thesis'presents'a'theoretical'lens'that'is'used'to'anchor' the'subjects'of'the'studies'in'‘built'environment’,'‘people’'and'‘road'signs’'through' the'theories'of'mobility'and'geosemiotics.' 'The' fields' of'mobility' and'geosemiotics' are' important' aspects' of' this' research.' They' provide' another' theoretical' challenge' in' the' form' of' merging' these' two' disciplines' in' the' analysis' in' order' to' enhance' a' dialogue' between' the' fields' of' urban'design'and'visual'communication'practices.'Thus,'the'interrelation'between' the' two' theories' will' help' to' answer' the' question' of' whether' road' signs' have' significant'impact'on'human'behaviour'when'moving'in'urban'settings.'In'order'to' understand' the' importance' of' visual' understanding' among' people,' focus' group' interviews,' design' manual' intervention' field' observations' and' were' conducted' during' the' research' process.' The' methods' were' conducted' within' controlled' settings' as' well' as' urban' settings' that' emphasised' the' interaction' between' the' participants'and' the'visual' representations' of' road' signs.'The'key' contribution' of' the' findings' in' this' research' project' is' the' methodological' triangulations' of' qualitative' data' used' in' the' focus' group' interviews,' the' visual' documentation' of' design' manual,' and' field' observations' which' were' inspired'by 'mobility' and 'geosemiotics' theories. 'This'thesis'aims'to'be'used'as'a'guideline'for' the'urban'planning'of'Malaysian'road'traffic'sign'system'in'the'future.'